2001
DOI: 10.1073/pnas.061034498
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive two-hybrid analysis to explore the yeast protein interactome

Abstract: Protein-protein interactions play crucial roles in the execution of various biological functions. Accordingly, their comprehensive description would contribute considerably to the functional interpretation of fully sequenced genomes, which are flooded with novel genes of unpredictable functions. We previously developed a system to examine two-hybrid interactions in all possible combinations between the Ϸ6,000 proteins of the budding yeast Saccharomyces cerevisiae. Here we have completed the comprehensive analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

88
2,543
2
13

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,281 publications
(2,676 citation statements)
references
References 33 publications
88
2,543
2
13
Order By: Relevance
“…Several observations indicate that Dhh1p has one or more additional roles in mRNA metabolism outside of mRNA turnover+ First, although the defect in mRNA decapping is the same at all temperatures (data not shown), dhh1⌬ strains are unable to grow at 18 8C and 36 8C+ This is in contrast to mutants completely blocked for decapping such as dcp1⌬ or dcp2⌬, which in our strain background are viable but slow growing at 18 8C and 36 8C Dunckley & Parker, 1999)+ Given this, the thermosensitivity of dhh1⌬ strains suggests Dhh1p has a second biological role+ Similarly, disruption of caf20⌬ in a dhh1⌬ background suppresses the cold-sensitive phenotype of dhh1⌬ cells without suppressing the mRNA decay defect+ In addition, we have observed that point mutations in the helicase motifs in Dhh1p allow growth at all temperatures even though mRNA decay is still defective (data not shown)+ One possibility is that this second function relates to some aspect of mRNA translation+ We also show that overexpression of Caf20p, which inhibits cap-dependent translation, is lethal to dhh1⌬ and pat1⌬ cells (Fig+ 6)+ Importantly, this effect is specific for the dhh1⌬ and pat1⌬ mutants and overexpression of Caf20p does not exaggerate the slow growth of other strains with defects in mRNA turnover such as lsm1⌬, ccr4⌬, and dcp2⌬ (Fig+ 6)+ This phenotype is suggestive of some role in translation for Dhh1p and Pat1p because overexpression of Caf20p is also lethal to cells defective in the translational initiation factors eIF-4E, eIF-4A, eIF-4B, and eIF-4G (de la Cruz et al+, 1997)+ Consistent with this interpretation, Pat1p has been suggested to be involved in translation initiation based on in vitro effects and alteration in polysomes profiles in vivo in pat1⌬ mutants (Wyers et al+, 2000)+ However, in our strain background, polysome profiles are largely unaffected in both dhh1⌬ and pat1⌬ strains as compared to wild type (data not shown)+ This implies that any roles of these proteins in translation are limited or transcript specific+ This is consistent with the fact that neither Dhh1p nor Pat1p is essential for viability+ Alternatively, Dhh1p's second biological role may be related to some aspect of mRNA transport+ Minshall et al+ (2001) have shown that clam RCK/p54 helicase p47 translocates from cytoplasm to the nucleus during early embryogenesis+ Consistent with this observation, Pat1p physically binds both Dhh1p and Crm1p/Xpo1p, an exportin (Ito et al+, 2001)+ In this light, the genetic relationship seen between Dhh1p and Caf20p could be explained if dhh1⌬ mutants are defective in some aspect of mRNA transport, thus reducing translational efficiency+…”
Section: Dhh1p Has a Second Biological Rolementioning
confidence: 61%
“…Several observations indicate that Dhh1p has one or more additional roles in mRNA metabolism outside of mRNA turnover+ First, although the defect in mRNA decapping is the same at all temperatures (data not shown), dhh1⌬ strains are unable to grow at 18 8C and 36 8C+ This is in contrast to mutants completely blocked for decapping such as dcp1⌬ or dcp2⌬, which in our strain background are viable but slow growing at 18 8C and 36 8C Dunckley & Parker, 1999)+ Given this, the thermosensitivity of dhh1⌬ strains suggests Dhh1p has a second biological role+ Similarly, disruption of caf20⌬ in a dhh1⌬ background suppresses the cold-sensitive phenotype of dhh1⌬ cells without suppressing the mRNA decay defect+ In addition, we have observed that point mutations in the helicase motifs in Dhh1p allow growth at all temperatures even though mRNA decay is still defective (data not shown)+ One possibility is that this second function relates to some aspect of mRNA translation+ We also show that overexpression of Caf20p, which inhibits cap-dependent translation, is lethal to dhh1⌬ and pat1⌬ cells (Fig+ 6)+ Importantly, this effect is specific for the dhh1⌬ and pat1⌬ mutants and overexpression of Caf20p does not exaggerate the slow growth of other strains with defects in mRNA turnover such as lsm1⌬, ccr4⌬, and dcp2⌬ (Fig+ 6)+ This phenotype is suggestive of some role in translation for Dhh1p and Pat1p because overexpression of Caf20p is also lethal to cells defective in the translational initiation factors eIF-4E, eIF-4A, eIF-4B, and eIF-4G (de la Cruz et al+, 1997)+ Consistent with this interpretation, Pat1p has been suggested to be involved in translation initiation based on in vitro effects and alteration in polysomes profiles in vivo in pat1⌬ mutants (Wyers et al+, 2000)+ However, in our strain background, polysome profiles are largely unaffected in both dhh1⌬ and pat1⌬ strains as compared to wild type (data not shown)+ This implies that any roles of these proteins in translation are limited or transcript specific+ This is consistent with the fact that neither Dhh1p nor Pat1p is essential for viability+ Alternatively, Dhh1p's second biological role may be related to some aspect of mRNA transport+ Minshall et al+ (2001) have shown that clam RCK/p54 helicase p47 translocates from cytoplasm to the nucleus during early embryogenesis+ Consistent with this observation, Pat1p physically binds both Dhh1p and Crm1p/Xpo1p, an exportin (Ito et al+, 2001)+ In this light, the genetic relationship seen between Dhh1p and Caf20p could be explained if dhh1⌬ mutants are defective in some aspect of mRNA transport, thus reducing translational efficiency+…”
Section: Dhh1p Has a Second Biological Rolementioning
confidence: 61%
“…Figure 3a relates predicted interactions at various confidence levels with the GSP interactions and the estimated superset of all human protein-protein interactions. The result of nearly 40,000 predicted interactions with a false positive rate of 50% and more than 10,000 predicted interactions with a false positive rate of just 20% is comparable or superior to the results of highthroughput experimental approaches in model organisms [13][14][15][16][17][18] . To examine the validity of this model, we binned predicted interactions by LR comp and assessed the true likelihood ratios for each bin, based on the intersection with the GSP and GSN (Fig.…”
Section: Integrative Analysis: Naive Bayes Classifiermentioning
confidence: 68%
“…From the Database of Interacting Proteins (DIP) 1 , we queried high-throughput interactome data from three model organisms: Sacchromyces cerevisiae [13][14][15][16] , Caenorhabditis elegans 17 and Drosophila melanogaster 3 . The S. cerevisiae interactome (SC) data comprised four high-throughput interactome data sets [13][14][15][16] and several low-throughput experiments, whereas the D. melanogaster (DM) and C. elegans (CE) data comprised one yeast two-hybrid data set each 17,18 .…”
Section: Model Organism Protein-protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…YBR262c encodes a protein similar to the calcium-calmodulin (CaM) binding protein kinase of apple. It was recently reported that YGR262c interacts in two-hybrid analysis with YCR099c, which displays a high level of similarity to the gene encoding the CPY receptor VPS10 (Ito et al, 2001). The phosphorylation of Vps10p (or homologues) by Ygr262cp, regulating its trafficking, may be responsible for the CPY secretion defect of ygr262D cells.…”
Section: Some Deletants Display Cpy Secretion But No P2 Cpy Accumulationmentioning
confidence: 99%